Efektivitas Beberapa Fungi Mikoriza Arbuskular Pada Pertumbuhan Batang Bawah Tanaman Karet (Hevea brasiliensis [Mull.] Arg.) - Yunita Siwi Palupi; Maria Viva Rini; Sri Yusnaini (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2022)
One way to increase latex production is by preparing and planting quality rubber seeds. Quality seeds can be seen from good physical appearance, short production life, and able to produce optimal latex. Quality seeds can be produced from good vegetative propagation. One of the vegetative propagation that is done to multiply rubber plants is by grafting or sticking buds. The research was carried out in two stages. The first stage was conducted to determine the effect of various types of mycorrhizae on the growth of the rootstock of rubber plants. While the second stage of research was conducted to determine the effect of several types of mycorrhizae on the success of grafting rubber plants. The results of the first stage of the study showed that the growth of rubber rootstock seedlings increased by the application of several types of AMF, such as the variables of plant height, stem diameter, root length, shoot wet weight, root wet weight, root volume, crown dry weight, and percentage of root infection. The administration of several different types of AMF had a significantly different effect on the percent of root infection by mycorrhizae with the highest percent of infection by AMF type Enthrospora sp.3 of 29.35% Glomus sp.2 of 26.33%, Entrophospora sp. 2 is 25.45%, and Glomus sp.3 is 17.35%.